(untitled) (Proceedings OPTIMAL, 2024)
One of the nutritional problems faced by adolescents is anemia. The World Health Organization mentions the prevalence of anemia almost evenly in various regions of the world, which ranges from 40-88%. About 25-40% of young women in Southeast Asia suffer from anemia. The purpose of this research is to analyze the effect of giving extracts of kelakai (Stenochlaena palustris) on the incidence of anemia in young women. This research is Quasi Experimental research with research design used is non equivalent pre and posttest control group design in young women who are anemic. The sampling techniques in this study used purposive sampling techniques. The number of samples in this study amounted to 30 respondents, divided into 15 subjects for the consumption of extracts (Stenochlaena palustris) (250mg) and 15 subjects consumed Ferrous fumarate tablets (60 mg) taken daily during the week. Hypothesis testing is done using paired T-test and independent t-test. The results of the paired t-test showed that there was a significant difference in the increase in hemoglobin levels in young women before and after treatment with p-value of 0.000 (<0.005), while the independent t-test showed that the difference Significant hemoglobin levels with an average difference of 2,283 and from statistical test results obtained values of 0.030 which can be concluded that there is a significant difference in the increase in hemoglobin levels in young women between the control and treatment groups. The conclusion in this study is that there is an influence of giving extracts to increase hemoglobin levels in young women. The advice in this study is to be able to use the future as an alternative in preventing anemia in young women.